1986
DOI: 10.1083/jcb.103.6.2467
|View full text |Cite
|
Sign up to set email alerts
|

The role of the main noncollagenous domain (NC1) in type IV collagen self-assembly.

Abstract: Abstract. Type IV collagen incubated at elevated temperatures in physiologic buffers self-associates (a) via its carboxy-terminal (NC1) domain, (b) via its aminoterminal (7S) domain, and (c) laterally; and it forms a network. When examined with the technique of rotary shadowing, isolated domain NC1 was found to bind along the length of type IV collagen to four distinct sites located at intervals of •100 nm each. The same 100-nm distance was observed in domain NC1 of intact type IV collagen bound along the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…Emerging evidence suggests that the C-terminal propeptide of the procollagen molecules plays a key role in the chain-specific recognition (3)(4)(5)(6)(7)(8). Bulleid and colleagues (9) demonstrated that transferring the C-propeptide of pro-␣1(III) chain to the corresponding region of the naturally heterotrimeric pro-␣2(I) molecule was sufficient to direct the new hybrid molecules to form stable homotrimers.…”
mentioning
confidence: 99%
“…Emerging evidence suggests that the C-terminal propeptide of the procollagen molecules plays a key role in the chain-specific recognition (3)(4)(5)(6)(7)(8). Bulleid and colleagues (9) demonstrated that transferring the C-propeptide of pro-␣1(III) chain to the corresponding region of the naturally heterotrimeric pro-␣2(I) molecule was sufficient to direct the new hybrid molecules to form stable homotrimers.…”
mentioning
confidence: 99%
“…For the NC1 domain we were able to indicate the presence of cross-linking by showing trimers (highmolecular weight material at 90 kD) and tetrameres (high-molecular weight material at 110 kD). These aggregates cannot found be in native tissue [30,44].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of Anti-NC1 Antibodies and Their Fab FragmentsAnti-NC1 antibodies were produced as described previously (29). Briefly, isolated NC1 in complete Freund's adjuvant was injected subcutaneously in female New Zealand rabbits three times at two-week intervals.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured in Dulbecco's minimal essential medium (DMEM) supplemented with 20% fetal calf serum (Sigma), 15 mM HEPES, 25 mM glucose, and antibiotics amphotericin (0.25 g/ml), penicillin G (100 IU/ml), and streptomycin (100 g/ml). Cells were used through passage 5-9, grown in T-75 flasks till 75-80% confluence, and then metabolically labeled for 18 h with 0.5 mCi of Isolation and Purification of Type IV Collagen and Type IV Collagen Domains-COL-IV was isolated from (EHS) as described previously (29). The major triple helix-rich domain, which lacks the NC1 and 7 S domains, was obtained by a light digestion of EHS-derived COL-IV with pepsin (Cooper Biomedical Inc.) as described by Yurchenco and Furthmayr (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation